Rational design and synthesis of some PPAR-γ agonists: Substituted benzylideneamino-benzylidene-thiazolidine-2, 4-diones. (April 2017) - Chhajed, Santosh S.; Chaskar, Shital; Kshirsagar, Sanjay K.; Haldar, G.M Animeshchandra; Kar Mahapatra, Debarshi
Abstract: The peroxisome proliferator activator receptor-γ (PPAR-γ) remained the most successful target for management of diabetes mellitus. The present work endeavors rational designing of some novel PPAR-γ agonists bearing benzylideneamino-benzylidene-thiazolidine-2, 4-dione scaffold. The research involved virtual screening of 37 different molecules by molecular docking studies performed by Molecular Design Suite (MDS) into the ligand binding domain of PPAR-γ receptor to explore the binding affinity and conformations of the molecules. Eight compounds; TZD1, TZD-4, TZD-7, TZD-16, TZD-25, TZD-28, TZD-34, and TZD-37 demonstrated high affinity for PPAR-γ binding site. The following compounds were taken into the account and synthesized using a multi-step synthesis protocol. The purity of the synthesized compounds was ascertained by sophisticated analytical techniques such as IR, NMR, Mass and elemental analysis. The compounds were tested for glucose uptake assay by using 3T3-L1 cell lines, where all the candidates exhibited nearly similar potential for uptake of glucose into the lines as that of standard drug rosiglitazone. Three molecules; TZD-1, TZD-4, and TZD-34 showed most prominent activity over hyperglycemic control. This research opened new avenues for smart designing of molecules with high efficiency towards the management of hyperglycemia.